Severe Dengue or Covid-19 Related MIS-C? Diagnostic Challenges in Resource-Limited and Dengue-Endemic Regions - Angelina; Dewi, Arfianti Chandra (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
Besides serological cross-reactivity and co-infection between dengue and SARS-CoV-2, diagnostic challenges arise because many people have had positive dengue IgG in dengue-endemic regions, and patients usually come after 4-5 days of fever. We report a case of 9-year-old girl, diagnosed with dengue with warning signs on admission because of fever, severe abdominal pain, thrombocytopenia, and positive dengue IgG. The subsequent course of the illness was not consistent with dengue infection because the shock happened during the febrile phase concurrent with rising leucocyte and platelet counts, the fever continued for longer than seven days, and there was bilateral non-purulent conjunctivitis with subconjunctival hemorrhage. She was diagnosed with MIS-C because of positive SARS-CoV-2 IgG and hyperinflammatory markers. Her clinical condition improved progressively after steroid administration. Clinical awareness about MIS-C is required to avoid misdiagnosis and improper treatment during or after the COVID-19 pandemic. Every clinician should consider MIS-C as a differential diagnosis if patients have inconsistencies with the course of dengue illness.